MULTIKULTURALISME PESERTA DIDIK MUSLIM DI YOGYAKARTA - A. M. Wibowo (Badan Litbang dan Diklat Kementerian Agama RI, 2018)
ABSTRACTThis study attempts to measure the multiculturalism of Muslimsstudent in high school level in Special region of Yogyakarta as the impact of the implementation of Islamic religious education in the School. Multiculturalism measured includes multiculturalism of Muslim students in high school (SMA), vocational (SMK) and Madrasah Aliyah (MA) education units in urban and rural areas. The focus of this research was conducted in Yogyakarta City and Kulonprogo Regency of Yogyakarta Special Region with Working Hypothesis (H1) (1) there is difference of multiculturalism of Muslim students between high school students, SMK, MA between urban and rural, (2) there is difference of multiculturalism of Muslims Student SMA, SMK, MA is seen from urban and rural, (3) there is interaction between the type of school and school location (rural or urban). By using quantitative research method with two way analysis tool of anova, this research has found 3 findings that are (1) there is difference of multiculturalism of Muslim students between SMA, SMK and MA students, (2) there is difference of multiculturalism level between school in urban and rural areas, where Muslimsstudent in rural schools are more multicultural than students who attend school in urban areas, (3) there is no interaction between the type of education and the area of multicultural education. ABSTRAKPenelitian ini mencoba mengukur multikulturalisme peserta didik muslim pada satuan pendidikan setingkat SMA di Daerah Istimewa Yogyakarta sebagai dampak dari implementasi pendidikan agama Islam di Sekolah. Multikulturalisme yang diukur mencakup uji beda multikulturalisme peserta didik muslim pada satuan pendidikan SMA, SMK, dan Madrasah Aliyah di perkotaan maupun di pedesaan. Lokus penelitian ini dilakukan di Kota Yogyakarta dan Kabupaten Kulonprogo Daerah Istimewa Yogyakarta dengan Hipotesa kerja (H1) (1) terdapat perbedaan multikulturalisme peserta didik muslim antara peserta didik SMA, SMK, MA antara di perkotaan dengan di pedesaan, (2) terdapat perbedaan multikulturalisme peserta didik Muslim SMA, SMK, MA dilihat dari perkotaan dan Pedesaan, (3) terdapat interaksi antara jenis sekolah dan letak sekolah (pedesaan atau perkotaan). Dengan menggunakan metode penelitian kuantitatif dengan alat uji analisis two way anova penelitian ini berhasil menemukan 3temuan yaitu (1) terdapat perbedaan multikulturalisme peserta didik muslim antara peserta didik SMA, SMK dan MA, (2) terdapat perbedaan tingkat multikulturalisme antara sekolah yang berada di perkotaan dan pedesaan, dimana muslim yang bersekolah di pedesaan lebih multiculturalis dibandingkan yangbersekolah di perkotaan, (3) tidak terdapat interaksi antara jenis pendidikan dan wilayah terhadap pendidikan multikultural.